An integral representation of the Catalan numbers - Shi, Xiao-Ting; Liu, Fang-Fang; Qi, Feng (Global Journal of Mathematical Analysis, 2015)
In the paper, the authors establish an integral representation of the Catalan numbers, connect the Catalan numbers with the (logarithmically) complete monotonicity, and pose an open problem on the logarithmically complete monotonicity of a function involving ratio of gamma functions.